2014
DOI: 10.4161/21623945.2014.960694
|View full text |Cite
|
Sign up to set email alerts
|

Propionic acid and butyric acid inhibit lipolysis and de novo lipogenesis and increase insulin-stimulated glucose uptake in primary rat adipocytes

Abstract: Fermentation of dietary fibers by colonic microbiota generates short-chain fatty acids (SCFAs), e.g., propionic acid and butyric acid, which have been described to have “anti-obesity properties” by ameliorating fasting glycaemia, body weight and insulin tolerance in animal models. In the present study, we therefore investigate if propionic acid and butyric acid have effects on lipolysis, de novo lipogenesis and glucose uptake in primary rat adipocytes. We show that both propionic acid and butyric acid inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 54 publications
5
58
0
3
Order By: Relevance
“…The finding that isobutyric acid significantly increased both basal and insulin-stimulated glucose uptake is in agreement with recently obtained results for propionic acid and to some extent also for butyric acid in rodent primary and differentiated adipocytes 33 . Phosphorylation of PKB is one key event in insulin-induced glucose uptake, 41 however, phosphorylation of PKB was shown to be downregulated by both branched and non-branched SCFAs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The finding that isobutyric acid significantly increased both basal and insulin-stimulated glucose uptake is in agreement with recently obtained results for propionic acid and to some extent also for butyric acid in rodent primary and differentiated adipocytes 33 . Phosphorylation of PKB is one key event in insulin-induced glucose uptake, 41 however, phosphorylation of PKB was shown to be downregulated by both branched and non-branched SCFAs.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that BSCFAs decrease the rate of de novo lipogenesis, 54 measured as the incorporation of [ 3 H]-labeled glucose into cellular lipids, is in agreement with previous results with non-branched SCFAs 33 . Altogether, these findings indicate that BSCFAs and SCFAs facilitate storage of diet-derived lipids in adipocytes rather than performing de novo synthesis, which at least under conditions of fat over-consumption appears metabolically beneficial.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies suggested that in addition to effects on skeletal muscle and liver metabolism, microbial products might affect lipid storage [6,7] and lipolysis [8,9] in the adipose tissue. External alterations of the gut microbiota composition (i.e.…”
Section: Introductionmentioning
confidence: 99%